OPTIMIZATION OF THE NATIONAL SYSTEM OF PHYSICAL TRAINING AND SPORTS GTO THROUGH A COMPARATIVE STUDY OF THE RESULTS OF TESTS OF PERSONS WITH MUSCULOSKELETAL DISORDERS - Evseev S.P. ,; Aksenov A.V. ,; Kryukov I.G. ,; Aksenova S.S. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to determine ways to improve the All-Russian Physical Culture and Sports Complex GTO for people with disabilities and individuals with limited health capabilities, taking into account the specifics of fulfilling the standards of tests for people with musculoskeletal disorders. Methods and structure of the study. Analysis of the results of testing people with disabilities and individuals with limited health capabilities with musculoskeletal disorders in the Russian Federation based on statistical reporting from the Federal Operator of the All-Russian Physical Culture and Sports Complex GTO for the period from 2019 to 2023. Results and conclusions. Based on the results of the work carried out – an analysis of the results of participation of persons with musculoskeletal disorders in the All-Russian Physical Culture and Sports Complex GTO for the period 2019-2023 – it is recommended to develop separate tests and introduce relative standards based on a comparison of their current level of physical fitness and initial indicators, using an individual approach to each participant.